Application of a Stable and Soluble Dibenzylbarium Reagent in the Synthesis of a Barium Imido Cluster - Rösch, Bastian; Martin, Johannes; Eyselein, Jonathan; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Organometallics, 2021)
The complex (DMAT)2Ba·(THF)2 (DMAT = 2-dimethylamino-α-trimethylsilylbenzyl) was prepared by a salt metathesis reaction between (DMAT)K and BaI2 in THF, and crystals were isolated in 83% yield. This monomeric complex dissolves well in aromatic or ethereal solvents and is also stable at higher temperatures in solution. Structural details and NMR parameters reveal a high degree of charge delocalization in the DMAT aryl ring. Comparison with identical Ca and Sr complexes, (DMAT)2Ae·(THF)2 (Ae = Ca and Sr), shows that the extent of delocalization increases down group 2: Ca < Sr < Ba. Due to chirality at the benzylic carbon, in solution the heterochiral R,S-isomer and homochiral R,R/S,S-isomers exist in equilibrium. A temperature-dependent NMR study gives an estimate of the Ae-C and Ae-N bond energies which decrease down the group: Ca > Sr > Ba. Although the DMAT carbanion is stabilized by resonance and negative hyperconjugation, (DMAT)2Ba·(THF)2 is still a very potent deprotonation reagent. Double deprotonation of Ph3SiNH2 gave the first Ba imido complex. A similar reaction using (DMAT)2Sr·(THF)2 gave the analogue Sr imido complex. Comparison with reported structures shows trends for the full series [(Ph3SiN)Ae·(THF)]4 (Ae = Mg, Ca, Sr, and Ba) which crystallize as tetramers with very stable, ionically bound heterocubane Ae4N4 cores.
CRIS-Team Scopus Importer:2021-06-04